Catch and Discards Rate with Catch Composition of Commercially Operated Multi-Day Trawlers Off Raigad Coast of Maharashtra - B.R. Kharatmol; S.S. Ghatge; A. S. Kulkarni; V.B. Sutar; A.T. Landage; L. Shenoy (Journal of Indian Fisheries Association, 2021)
The commercially-operated multi-day trawlers from the Raigad coast carry out fishing operations between 180 10'25” N to 19020'35” N latitude and 720 45'11” E to 730 30'00” E longitude in the mean depth range of 12 m to 52 m. A study was carried out during two fishing seasons, i.e., 2016-17 and 2017-18, to estimate the catch composition, changing catch rates, discards, fishing fleet, and operation. Major catch composition of multi-day trawlers comprised of Rastrelliger kanagurta, Lepturacanthus savala, Otolithus cuvieri, Harpodon nehereus, Coilia dussummieri, Arius maculatus, Penaeid prawns, Lactarius lactarius, Scomberomorus guttatus, and non- penaeid prawns. The average catch rates by multi-day trawlers were found to be 32.65 kg/h and the average discards of 7.63 kg/h. Discards comprised juveniles of commercial species and adults of low market value fishes. Cod-end mesh size of trawl net varied from 15 to 25 mm depending on the fishery resources harvested. The t-Test performed on fish catch and discard of multi-day trawlers showed a statistically significant diﬀerence (p